Discrimination, exclusion and environmental harm: Why EU lawmakers need to ban freight transport restrictions to save the Single Market - Matthias Bauer (European Centre for International Political Economy (ECIPE), 2020)
The EU's Mobility Package 1 legislative proposal was once intended to improve the working conditions of truck and small-van drivers in the EU. Initially, the European Commission also aimed at securing a smooth and non-discriminatory functioning of the Single Market. Some provisions of the current package may indeed have a positive impact on drivers' working conditions, e.g. limits on working time and obligatory rest periods. However, over the past three years, the legislative procedure towards the current draft of the Mobility Package 1 was hijacked by the protectionist agenda of Western Europe's haulage and logistics businesses. Spearheaded by the French government, some national governments and Members of the European Parliament called for tighter freight cabotage and return-to-home provisions to shield Western European transport markets against competition from other EU Member States. The proposed restrictions to cross-border trade in the European Single Market are up for a vote in the European Parliament in mid-2020.
Keywords: 330; Güterverkehr; Arbeitsbedingungen; Logistikdienstleister; Regulierung; Internationaler Wettbewerb; EU-Binnenmarkt